Biomimetic asymmetric reduction of benzoxazinones and quinoxalinones using ureas as transfer catalysts. Issue 53 (1st June 2020) - Zhao, Zi-Biao; Li, Xiang; Chen, Mu-Wang; Zhao, Zongbao K.; Zhou, Yong-Gui
Abstract : Using ureas as transfer catalysts through hydrogen bonding activation, biomimetic asymmetric reduction of benzoxazinones and quinoxalinones has been developed, giving chiral products with high enantioselectivities. A key dihydroquinoxalinone intermediate of a BRD4 inhibitor was synthesized using biomimetic asymmetric reduction. Abstract : Using ureas as transfer catalysts through hydrogen bonding activation, biomimetic asymmetric reduction of benzoxazinones and quinoxalinones with chiral and regenerable NAD(P)H models was described, giving chiral dihydrobenzoxazinones and dihydroquinoxalinones with high yields and excellent enantioselectivities. A key dihydroquinoxalinone intermediate of a BRD4 inhibitor was synthesized using biomimetic asymmetric reduction.